Design of Software for Digital Multimeter Calibration Based on Labwindows/CVI. Issue 4 (December 2018) - Zhenjie, Zeng; Zhu, Xiaofei; Shen, Xiaowei; Wu, Kai; Qi, Shiju
Abstract: The digital multimeter is a common instrument in the metrology department calibration. In order to improve the efficiency of verification and calibration, the automatic calibration software is developed based on the Labwindows/CVI platform, by using the SCPI programming method under the VISA architecture, and by means of the instrument driver programming. It realizes the automatic calibration of different types of digital multimeters, and transforms the work done by the original manual operation instrument into the software control instrument automatically, which greatly improves the work efficiency.